Quality of antenatal care provided by nurse midwives in an Urban health centre with regard to low-risk antenatal mothers - Ruby Angeline Pricilla; Kirubah Vasandhi David; Rajeswari Siva; T Jeni Christal Vimala; Sajitha Parveen MF Rahman; Nancy Angeline (Wolters Kluwer Medknow Publications, 2017)
Background:India contributes to 19% of the global maternal deaths. Good quality antenatal care can prevent maternal deaths by early detection of complications and maintaining maternal health. There are few studies documenting quality of antenatal care in India. This study aimed to document the antenatal services provided by nurse midwives to low-risk pregnant mothers from an urban population. Aims: The primary objective was to describe the quality of the antenatal care provided by nurse midwives of an urban health centre with regard to low-risk mothers. The secondary objective was to document the maternal and early neonatal outcomes of the enrolled mothers during the period of study. Methods: This prospective cohort study was done on 200 pregnant women who had antenatal care by nurse midwives between April 2014 and November 2014. The quality of care was assessed by a checklist adapted from World Health Organization (WHO). Results: We report that the quality of antenatal care for all domains was above 90% except for the health education domain, which was poor with regard to breastfeeding and family planning in the enrolled 200 pregnant women. Conclusion: Our study concluded that trained nurse midwives when regularly monitored, audited and linked with reliable referral facilities can deliver good quality antenatal care.